Germination of Albizia hassleri seeds at different temperatures, under laboratory conditions - Soto Gonzales, Jose Luis [UNESP]; Valiengo Valeri, Sergio [UNESP]; Cesar de Paula, Rinaldo [UNESP] (Univ Austral Chile, Fac Ciencias Forestales, 2010)
The objective of this study was to analyze the germination of seeds of Albizia hassleri under different temperatures. A completely random design arranged as a split plot for temperatures regimes, with 11 seed lots and four replications of 15 seeds was used. The plot was represented by the various lots and the sub plots for different temperatures. The means were compared by Scott-Knott test at 5% probability. The temperatures used were: a) constant: 20, 25 and 30 degrees C, and b) alternating: 20-30 and 25-35 degrees C. For all 11 seed lots the mean germination was 90%, speed germination index (IVG) was 5.059, fresh matter of seedlings (MMF) was 0.0628 g and dry matter (MMS) 0.0499 g. The variation coefficient (CV) between plots ranged from 8.48% for germination to 51.71% for dry matter of seedlings and sub plot of 6.77% to 60.45% for germination and MMS. These high values of CV, tested for MMS and MMF, indicate low repeatability of results within each treatment. In general, the IVG obtained at temperatures of 20 and 25 degrees C was lower than those in temperatures of 30, 20-30 and 25-35 degrees C. The best temperature for IVG was the alternating 25-35 degrees C and constant 30 degrees C. The germination test can be conducted at 30, 20-30 and 25-35 degrees C for 19 days.
Keywords: forest seeds; native species; germination temperatures